2023
DOI: 10.1002/advs.202303165
|View full text |Cite
|
Sign up to set email alerts
|

Macroscopic Quantum Tunneling of a Topological Ferromagnet

Abstract: The recent advent of topological states of matter spawned many significant discoveries. The quantum anomalous Hall (QAH) effect is a prime example due to its potential for applications in quantum metrology, as well as its influence on fundamental research into the underlying topological and magnetic states and into axion electrodynamics. Here, electronic transport studies on a (V,Bi,Sb) 2 Te 3 ferromagnetic topological insulator nanostructure in the QAH regime are presented. This allows access to the dynamics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
(78 reference statements)
0
3
0
Order By: Relevance
“…A key question to be addressed is to determine the minimum size limit below which the QAH effect breaks down. Recent work has demonstrated that the quantization is well preserved in the deep sub-micrometer size limit [56][57][58]. For example, when the MTI films were patterned into miniaturized Hall bar devices with a sub-µm channel width as shown in Figure 2a, the magnetic hysteresis loop of ρ xx and ρ xy still resembled the behavior in large-scale devices (Figure 2b,c) [56].…”
Section: Scaling Behavior During Quantum Phase Transitions In Finite-...mentioning
confidence: 87%
See 1 more Smart Citation
“…A key question to be addressed is to determine the minimum size limit below which the QAH effect breaks down. Recent work has demonstrated that the quantization is well preserved in the deep sub-micrometer size limit [56][57][58]. For example, when the MTI films were patterned into miniaturized Hall bar devices with a sub-µm channel width as shown in Figure 2a, the magnetic hysteresis loop of ρ xx and ρ xy still resembled the behavior in large-scale devices (Figure 2b,c) [56].…”
Section: Scaling Behavior During Quantum Phase Transitions In Finite-...mentioning
confidence: 87%
“…By measuring the temperature, current bias, and gate dependence, the breakdown of the QAH effect in finite-sized MTI samples can be attributed to bulk localized states mediated by the cross-channel back-scattering mechanism [56], as demonstrated in Figure 2d,e. In addition to quantized states, during the magnetic switching, telegraph noises due to magnetic fluctuations are also observed in sub-µm devices, and careful analyses of these noise spectrum give an estimated magnetic domain size of an ~100-200 nm range [56,58]. Whilst the quantization is persistent in quantized states in mesoscopic MTI devices, the scaling behavior shows a strong size dependence in the quantum critical regime during the topological phase transition [62].…”
Section: Scaling Behavior During Quantum Phase Transitions In Finite-...mentioning
confidence: 99%
“…In this article, we report a measurement scheme that improves the robustness of the zero-magnetic-field QAHE at higher currents 31 . This is achieved through the simultaneous injection of current into two disconnected perimeters of a multi-terminal Corbino device.…”
Section: Proof Of Conceptmentioning
confidence: 99%